2021
DOI: 10.1111/nin.12469
|View full text |Cite
|
Sign up to set email alerts
|

Optimising social conditions to improve autonomy in communication and care for ethnic minority residents in nursing homes: A meta‐synthesis of qualitative research

Abstract: A large proportion of nursing home residents in developed countries come from ethnic minority groups. Unmet care needs and poor quality of care for this resident population have been widely reported. This systematic review aimed to explore social conditions affecting ethnic minority residents' ability to exercise their autonomy in communication and care while in nursing homes. In total, 19 studies were included in the review. Findings revealed that ethno-specific nursing homes create the ideal social condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…Our ndings support two previous literature reviews which found creating cultural and linguistic congruent care is a social condition for residents to communicate their needs and preferences and ful l autonomy [5,15] . However, our study revealed that arranging bilingual staff to be available and accessible for residents during all shifts was not always possible in ethno-speci c nursing homes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our ndings support two previous literature reviews which found creating cultural and linguistic congruent care is a social condition for residents to communicate their needs and preferences and ful l autonomy [5,15] . However, our study revealed that arranging bilingual staff to be available and accessible for residents during all shifts was not always possible in ethno-speci c nursing homes.…”
Section: Discussionsupporting
confidence: 89%
“…This nding supports studies on Finnish ethno-speci c nursing homes in Sweden where rich resources to support residents' social engagement were developed through connections and collaborations with community organisations [7,30] . This nding also supports the suggestion that arranging residents from the same ethnic group in a unit of a mainstream nursing home, may be logistically viable in terms of encouraging socialisation among residents while developing resources to support culturally and linguistically congruent care [5,7] .…”
Section: Maintaining Meaningful Social Interactionssupporting
confidence: 76%
See 2 more Smart Citations
“…Second, there were also no studies that assessed the impact of culturally-77 or ethno-specific 78 nursing homes where care is tailored to a particular group, including through aspects such as staffing, offering specific foods and activities as well as building design. 79 Third, we found only five studies of community-level characteristics and most used census-derived measures of the population surrounding the home. A report of case studies from LTC homes in Canada, Norway, and Germany found that families and residents highlighted the importance of neighborhood amenities that allow residents to engage with the community and visitors.…”
Section: Discussionmentioning
confidence: 99%